Human ILC3 Exert TRAIL-Mediated Cytotoxicity Towards Cancer Cells - Siegler, Jana-Julia; Correia, Margareta P.; Hofman, Tomáš; Prager, Isabel; Birgin, Emrullah; Rahbari, Nuh N.; Watzl, Carsten; Stojanovic, Ana; Cerwenka, Adelheid (Frontiers in Immunology, 2022)
Group 3 helper Innate Lymphoid Cells (ILC3s) are cytokine-producing lymphocytes that respond to stress signals released during disturbed tissue homeostasis and infection. Upon activation, ILC3s secrete IL-22 and IL-17, and orchestrate immune responses against extracellular pathogens. Their role in cancer remains poorly explored. To determine their anti-cancer effector potential, we co-cultured cytokine-activated human ILC3s with cancer cells of different origins. ILC3s were able to directly respond to tumor cells, resulting in enhanced IFN-γ production. Upon tumor cell encounter, ILC3s maintained expression of the transcription factor RORγt, indicating that ILC3s preserved their identity. IILC3s were able to directly kill both hepatocellular carcinoma and melanoma tumor cells expressing cell-death receptor TRAILR2, through the activation of Caspase-8 in target cells. Moreover, liver-derived cytokine-activated ILC3s also expressed TRAIL and were able to eliminate hepatoblastoma cells. Together, our data reveal that ILC3s can participate in anti-tumor immune response through direct recognition of tumor cells resulting in IFN γ release and TRAIL-dependent cytotoxicity. Thus, ILC3s might be ancillary players of anti-tumor immunity in tissues, acting as primary responders against transformed or metastasizing cells, which might be further exploited for therapies against cancer.